Cross-National Analysis of Cultural Dimensions and their Effects on Suicide Rates - Hoang Dang Tam, Nam; Sokol, Ondřej; Formánek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis presents a thorough examination of global suicide rates, drawing on data from 183 nations spanning the period 2000 to 2019. Utilizing data visualization techniques, the study identifies trends and anomalies in suicide rates, then undertakes a causal analysis of those phenomenon. Additionally, a random effects (RE) model is estimated using data from 81 countries to explore the influence of Hofstede cultural dimensions and socio-economic factors on suicide rates. The analysis delves into how these factors contribute to gender-specific variations in suicide rates, with a particular emphasis on the influence of cultural values.
Vedoucí práce: Ondřej Sokol
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses